PREPARAÇÃO DE NOVOS DERIVADOS QUINOIDAIS CONTENDO O ANEL 1,2,3-TRIAZÓLICO E ESTUDO DA SUA ATIVIDADE ANTITUMORAL - DA SILVA, Natan; COUTO, Aliziane; SILVA, Carlos; BRAND, George; OLIVEIRA, Geane; VALENÇA, Wagner (ANAIS DO ENIC, 2026)
.